2021
DOI: 10.1029/2020je006790
|View full text |Cite
|
Sign up to set email alerts
|

Lunar Photoemission Yields Inferred From ARTEMIS Measurements

Abstract: Photoemission yield (the number of emitted electrons per incoming photon) is one of the fundamental properties of solid materials but is not yet well constrained for the lunar surface for photon energies >∼20 eV. In this study, we constrain this yield for incident photons with energies of ∼10–500 eV with data from the Acceleration, Reconnection, Turbulence, and Electrodynamics of the Moon's Interaction with the Sun (ARTEMIS) mission along with solar irradiance spectra from Version 2 of the Flare Irradiance Spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…(1972), and also two photoemission yields shown in Figure 7 in Xu et al. (2021) (referred as “high” and “low” yields because of the uncertainty in surface potentials). The modeled photoelectron energy spectra are shown as the green dashed lines in Figure 1, lower and higher fluxes corresponding to low and high photoemission yields, respectively.…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…(1972), and also two photoemission yields shown in Figure 7 in Xu et al. (2021) (referred as “high” and “low” yields because of the uncertainty in surface potentials). The modeled photoelectron energy spectra are shown as the green dashed lines in Figure 1, lower and higher fluxes corresponding to low and high photoemission yields, respectively.…”
Section: Methodsmentioning
confidence: 95%
“…To remove the possible contamination of PHE in our selected BSE cases, we employ the methodology described by Xu et al. (2021) to model the PHE energy spectrum. More specifically, we use the solar irradiance spectra from Version 2 of the Flare Irradiance Spectral Model (FISM2) (Chamberlin et al., 2007, 2008, 2020), the probability function adopted from Feuerbacher et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We first present a case study of ARTEMIS observations in the magnetotail lobe region (Figure 5). This event is one of the reported Auger electron events by Xu et al (2021) and was analyzed by Harada et al (2017), who derived the lunar surface potential U M of +15-25 V based on the observed energy-dependent loss cone of electrostatically reflected lobe ions (ion reflectometry). For a non-zero potential difference, we shift the 1-eV resolution model energy spectrum such that the distribution function is conserved, and the shifted spectrum is convolved with the instrument response to derive the model-predicted measurements.…”
Section: Observations In the Terrestrial Magnetotailmentioning
confidence: 99%
“…In this section, we briefly introduce one of the Auger electron observations reported by Xu et al. (2021). Figure 1 shows a case of Auger electron observations in the solar wind.…”
Section: Artemis Observationsmentioning
confidence: 99%